Literary for Children: The Values of â€œTri Hita Karanaâ€ in â€œYuyu yang Baikâ€ Story as Childrenâ€™s Character Education - Tantri, A.A.S; Bayu, G.W; Dewantara, I.P.M (Universitas Pendidikan Ganesha, 2020)
Having good knowledge, skills, and good character is the next generation of superior nation.Many ways can be taken to foster the character of the younger generation, such as through theapplication of the values of â€œTri Hita Karanaâ€ in the story of the â€œYuyu yang Baikâ€ by Cok Sawitri. Thisresearch is a qualitative descriptive study. This study contains the values of â€œTri Hita Karanaâ€ inâ€œYuyu's yang Baikâ€ story. Data was collected through data cards and analysed by the Mils andHuberman model. This model goes through three stages, namely: data reduction, data presentation,and drawing conclusions. The conclusion of this study is that character education can be taught toearly childhood based on the values of â€œTri Hita Karanaâ€ in â€œYuyu's yang Baikâ€.